A novel augmentation technique for the repair of full thickness gluteal tendon tears: a biomechanical analysis in an ovine model - Alexander Derksen; Zarife Balli; Henning Windhagen; Dennis Nebel; Janin Reifenrath (Journal of Orthopaedics and Traumatology)
Abstract Background Gluteus medius tendon tears lead to considerable functional limitations and a high level of suffering in affected patients. In cases where the symptoms are severe, surgical intervention is indicated. A range of techniques are used to repair the tendon, with the primary aim being to achieve the highest possible primary stability in order to minimise the risk of re-rupture. This biomechanical study compares two different refixation techniques in terms of their stability in an ovine model. Material and methods The gluteal tendons of sheep hips (n = 17) were meticulously prepared and detached from the femoral insertion. To reattach these tendons at their original anatomical footprint, either the sole double-row transosseous-equivalent technique (DR) or the DR supplemented by a proximal suture insertion (augmentation) of the tendon (DR +) was used. Pull-out tests were performed until failure using a uniaxial material testing machine, with a tensile force applied along the physiological tensile direction of the hip abductors. The data obtained (force at failure, linear stiffness) were compared between the groups using the Mann–Whitney U test. Results The augmentation of the proximal tendon portion resulted in a substantial increase in force at failure, exceeding 450% (698 ± 80.3 N DR + compared with 155.9 ± 53.9 N DR technique). In addition, augmented tendons exhibited a notable enhancement in stiffness, with an average increase of 31.3 ± 15 N/mm in DR + compared with 12.4 ± 4.8 N/mm in DR. Furthermore, the DR + method resulted in a substantial reduction in the incidence of slippage of the tendon fibres out of the sutures and tendon bundles when compared with the DR suture. Conclusions The clinical problem of suture knots becoming loose within the tendon stump, leading to the failure of the tendon sutures, could be mitigated by additional augmentation, resulting in a substantial increase in ultimate load at failure. The benefits of the double-row transosseous-equivalent technique, which facilitates the pressing of the tendon stump against the footprint, are maintained. Level of Evidence Level of Evidence 5